Revitalizing Gorontalo Vocabulary through Bilingual Comics in Coastal Environmental Contexts - Salman Alade; Ita Meiarni; Wa Ode Irawati; Wiwik Pratiwi; Fitriya Dessi Wulandari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The declining use of regional languages among children has become a growing concern in Indonesian communities, including Gorontalo, where intergenerational language transmission is increasingly disrupted by the dominance of national and global languages. Despite existing studies on comic-based learning and bilingual instruction, research integrating bilingual comics with local environmental contexts specifically for regional language revitalization among children remains limited. This study aims to examine the effectiveness of bilingual comic-assisted learning with coastal environmental contexts in improving children’s Gorontalo vocabulary acquisition. A pre-experimental one-group pretest-posttest design was employed involving 15 children aged 8–10 years in a coastal community of Gorontalo. Data were collected through validated vocabulary tests administered before and after two learning sessions using the bilingual comic Perahu dan Rahasia Air. The findings revealed substantial improvement: mean pretest score was 3.40, increasing to 8.87 posttest (mean gain = 5.47). A Wilcoxon signed-rank test confirmed the improvement was statistically significant (Z = −3.41, p < 0.001). Before the intervention, 73.3% of participants belonged to poor or very poor categories; after the intervention, 93.3% reached good or very good categories. The novelty of this study lies in its integration of bilingual comics, contextual environmental narratives, and regional language revitalization within children’s literacy practices. Findings suggest that culturally grounded bilingual visual media can support vocabulary acquisition and contribute meaningfully to regional language revitalization efforts. Limitations related to sample size and intervention duration are acknowledged, and directions for future research are discussed.